Assessment of Electronic Voting Technologies in election processes in Zimbabwe - Moyo, Nkosikhona; Vyas-Doorgapersad, Shikha (Journal of Ecohumanism, 2026)
The electoral system in Zimbabwe following independence is the main topic of this essay. Furthermore, it is crucial to consider the numerous stakeholders that directly influence Zimbabwe's electoral processes, such as political parties, political institutions and electoral bodies, as well as any other election-related concerns. The study is qualitative and is based on data that may be found online, in official papers, articles, and laws. Document review is used to gather the data, and document analysis is used to evaluate it further. The results verify that the general conduct of elections has been enhanced by the implementation of electronic voting technology, such as biometric voter registration, in Zimbabwe. To enhance the context of EVTs and preserve election integrity, the essay suggests maintaining the biometric voter registration (BVR) system and gradually integrating other information and communication technologies (ICTs) in other election-related domains.